Substance-abusing parents and their children in termination of parental rights cases in Israel. (July 2016) - Ben-David, Vered
Abstract: Parental substance abuse significantly increases the risk of child maltreatment and loss of custody. If parental capacity due to substance abuse cannot be rehabilitated within a limited time period and if the child cannot be safely returned to his/her home, the state, in various jurisdictions, is empowered to initiate termination of parental rights proceedings. Despite the connection between substance abuse and termination of parental rights, the research literature in this area is limited. Based on a sample of 212 rulings in favor of termination of parental rights by Israeli courts, the present study examines factors that differentiate substance-abusing from non-substance-abusing parents. The findings indicate that substance-abusing parents constitute a unique high-risk group among parents whose parental rights were terminated. This group is characterized by a higher cumulative risk that includes mental health issues with an emphasis on personality disorders and emotional problems, criminal records, child neglect and maternal single parenthood. All these factors, as well as the overall number of risk factors in a particular case, were found to predict substance-abusing parenthood. A discussion of the findings and their implications for social work practice with families involved in the child welfare system follows. Highlights: Substance abusing parents constitute a high-risk group among parents who were TPR. Substance-abusing parents were characterized by a higher cumulative risk. Substance-abusing parents had criminal records and maternal single parenthood. Substance-abusing parents presented a higher rate of child maltreatment. Substance-abusing parents had a higher rate of mental health problems.